Cavus Foot Deformity with Calcaneonavicular and Medial Cuneiform–Navicular Coalition: A Case Series - İNCESOY, MUSTAFA ALPER; İNCESOY M. A.; UZER, GÖKÇER; UZER G.; ORUJOV, SAİD; ORUJOV S.; ŞENARAN, HAKAN; Geckalan M. A.; ŞENARAN H. (My University, 2023)
Tarsal coalitions have only very infrequently been observed in the context of cavus foot abnormalities. Recognizing this diagnosis could be crucial to effective cavus repair. We report tarsal coalitions observed in cavus deformity here. Between 2022 and 2023, the records of every patient treated by one of the authors for a varus deformity who was later determined to have either a unilateral or bilateral tarsal coalition were examined. Two patients with cavus deformities who were treated by one of the authors have either a unilateral or bilateral tarsal coalition. Three foot (medial cuneiform–navicular n = 1 and calcaneonavicular n = 2) with tarsal coalition were examined. All of these cases occurred in patients with idiopathic cavus deformity. Computed tomography scans were used to make a firm diagnosis for each patient. We advise surgeons to keep an awareness for this potential comorbid issue in all cavus foot abnormalities and to take advanced imaging into consideration. In these uncommon cases, the medial cuneiform–navicular and calcaneonavicular joints formed an osseous coalition with pes cavus deformity, which successfully resolved with conservative and surgical treatment, respectively. Level of Clinical Evidence: IV.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Ortopedi ve Travmatoloji; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Orthopedics and Traumatology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ORTOPEDİ; Clinical Medicine (MED); CLINICAL MEDICINE; ORTHOPEDICS; Ortopedi ve Spor Hekimliği; Orthopedics and Sports Medicine; Calcaneonavicular coalition; Cavus foot; Medial Cuneiform–Navicular Coalition; Tarsal coalition